Digital Milieus: A Posthumanist Media Ecology for a Planetary Computation Era - Alonso, Joaquín Moreira (Journal of Posthumanism, 2024)
Media ecology introduced a fresh perspective to media studies, previously dominated by content analysis, effects research, ideologies, and flux studies. This approach allows us to understand media in a non-linear manner, seeing them as constructors of our everyday contexts rather than mere tools for specific purposes. Despite this shift, classical media ecology often views media as information transmitters for discrete human beings, rooted in modern humanist rationalism. This article suggests that a posthumanist approach to media ecology can help overcome modern anthropocentrism by studying the mutual ontogenesis between humans and their media environments. This change offers a fruitful framework for studying contemporary media, characterized by ubiquity, hyperconnection, and planetary-scale computing. The analysis emphasizes the interdependence between humans, technology, and the environment, highlighting the diminishing human agency amid automated systems and ubiquitous computing.